2022
DOI: 10.1039/d1nr06043k
|View full text |Cite
|
Sign up to set email alerts
|

Cerium oxide nanozyme attenuates periodontal bone destruction by inhibiting the ROS–NFκB pathway

Abstract: Periodontitis, an inflammatory disease of oxidative stress, occurs due to the excess reactive oxygen species (ROS) contributing to cell and tissue damage that in turn leads to alveolar bone resorption...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 58 publications
0
48
0
Order By: Relevance
“…During the treatment of ROS-related diseases, CeO 2 also plays roles in downregulating proinflammatory cytokine levels, upregulating anti-inflammatory cytokine levels, inhibiting the ROS–NFκB pathway, etc. 69 , 73 , 77 …”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
See 1 more Smart Citation
“…During the treatment of ROS-related diseases, CeO 2 also plays roles in downregulating proinflammatory cytokine levels, upregulating anti-inflammatory cytokine levels, inhibiting the ROS–NFκB pathway, etc. 69 , 73 , 77 …”
Section: Antioxidant Nanozymesmentioning
confidence: 99%
“…54,[57][58][59][60][61] Furthermore, they may serve as a novel therapy for neurodegenerative diseases, depression, ischemic stroke, autoimmune diseases, hepatic injury, sepsis, psoriasis, inflammatory bowel disease (IBD), periodontitis, and acute gout. [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77] Based on the excellent ROS eliminating capabilities of CeO 2 , researchers have explored various kinds of targeted methods to address the aforementioned diseases.…”
Section: Cerium Oxide (Ceria)-basedmentioning
confidence: 99%
“…[39][40][41][42] With the development of nanotechnology, scientists have synthesized a large number of functional nanomaterials that can mimic the intracellular antioxidant system to defend against ROS-induced damage. Nanomaterials, such as selenium-doped carbon quantum dots, [43] 2D vanadium carbide MXenzyme, [44] human serum albumin-Mn 3 O 4 , [45] atomically dispersed Cu, [46] Pt/CeO 2 , [47] ROS-sensitive nanozymeaugmented photoacoustic nanoprobe, [48] cerium oxide, [49] and Fe-curcumin-based nanoparticles, [50] have been used to scavenge ROS. The specificity and effectiveness of ROS scavengers and the fact that they can be personalized should contribute to the development of medical instruments, drugs, and diagnosis and treatment of multiple diseases that will improve the quality of life of patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several pieces of literature studies have shown that oxidative stress participates in occurrence and development of periodontitis. [5][6][7] Generally, reactive oxygen species (ROS) produced by immune cells exhibit antibacterial effects and regulate host defense and immunoregulation. 8 Nevertheless, excessive ROS can produce cytotoxic effects.…”
Section: Introductionmentioning
confidence: 99%